GESTION DES DECHETS MENAGERS ET SES CONSEQUENCES SOCIO-ECONOMICO-SANITAIRES : CAS DE LA VILLE DE KISANGANI EN REPUBLIQUE DEMOCRATIQUE DU CONGO. - BAELONGANDI, Augustin SOMBO (IJRDO - Journal of Business Management, 2021)
This article showed the sanitary state in the optics of the management of domestic garbage that is in a pitiable state capable to create illnesses of all kind to the inhabitants of the city of Kisangani in DRC. Facing this situation that changes to pathology in all developing countries, we challenge the conscience of our leaders, intellectual, services committed for hygiene, purification and healthiness to take their responsibilities each to his level for the communal well-being and for the future of the humanity.